The Influence of Organizational Culture, Motivation and Welfare on Employee Performance at PT Duta Persada Duper (Literature Review) - Gebian Ridho Sadewa (Dinasti International Journal of Management Science, 2023)
The Literature Review article entitled "The Influence of Organizational Culture, Motivation, and Welfare on Employee Performance" is a scientific paper whose aim is to develop a research hypothesis about the relationship between variables that will be used in subsequent research in Human Resource Management. This article was created using the library research method obtained from online sources such as Google Scholar, Mendeley, and other academic media. The results of this Literature Review article show that there are three main factors that influence employee performance, namely organizational culture, motivation, and well-being. First, a good organizational culture can improve employee performance because it provides clear guidelines and norms and makes employees feel motivated and have a common goal. Second, high motivation will lead to better employee performance because employees feel driven to achieve goals and feel valued for their performance. Third, employee welfare which includes health, good work environment, and fair compensation also has a positive impact on employee performance because employees feel valued and are motivated to work well. In the science of Human Resource Management, an understanding of these factors is very important to improve employee performance and achieve organizational goals effectively. This Literature Review article can be a reference for researchers and practitioners in the field of Human Resource Management to develop further research on the influence of these factors on employee performance.